2005
DOI: 10.1108/03090560510572016
|View full text |Cite
|
Sign up to set email alerts
|

Consumer evaluations of sales promotion: the effect on brand choice

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 34 publications
5
29
0
3
Order By: Relevance
“…Monetary promotions are considered the best alternative for short-term increased sales, and these promotions play a key role in consumer choices (Alvarez & Casielles, 2005). This assumption is reinforced by Blattberg and Neslin (1990), who argued that this promotion type satisfies consumers' desire for savings.…”
Section: Literature Review and Working Hypothesesmentioning
confidence: 80%
See 4 more Smart Citations
“…Monetary promotions are considered the best alternative for short-term increased sales, and these promotions play a key role in consumer choices (Alvarez & Casielles, 2005). This assumption is reinforced by Blattberg and Neslin (1990), who argued that this promotion type satisfies consumers' desire for savings.…”
Section: Literature Review and Working Hypothesesmentioning
confidence: 80%
“…Lee (2002), for instance, found that sales promotions are more effective than advertising in reaching company sales objectives. Nevertheless, studies conducted in the 1970s, such as Cotton and Babb (1978), and more recent studies such as Alvarez and Casielles (2005) have demonstrated the effectiveness of both monetary and nonmonetary sales promotions in consumers' responses and attitudes. For this reason, the following hypothesis is proposed: H1: Sales promotions positively influence consumers' purchase intentions.…”
Section: Literature Review and Working Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations